Pulmonary Hypertension in Heart Failure Patients - Rao, Sriram D (Card Fail Rev, 2020)
The development of pulmonary hypertension (PH) in patients with heart failure is associated with increased morbidity and mortality. In this article, the authors examine recent changes to the definition of PH in the setting of left heart disease (PH-LHD), and discuss its epidemiology, pathophysiology and prognosis. They also explore the complexities of diagnosing PH-LHD and the current evidence for the use of medical therapies, promising clinical trials and the role of left ventricular assist device and transplantation.